Hubungan antara Higiene Perorangan dan Kejadian Koinfeksi Cacingan pada Penderita Tuberkulosis - Shofia, Lailatis; Hermansyah, Bagus; Suswati, Enny; Agustina, Dini; Mufida, Diana Chusna; Shodikin, Muhammad Ali (Fakultas Kedokteran Universitas Sriwijaya, 2021)
Tuberculosis (TB) and intestinal worms are infectious diseases with a large number of sufferers in Indonesia. The high prevalence of intestinal worms in Indonesia allows the occurrence of STH coinfection in pulmonary TB patients which causes anti M. tuberculosis immunity to decrease so that the response to tuberculosis treatment is not optimal. One of the risk factors of STH infection is personal hygiene. The purpose of this study was to analyze the relationship between individual hygiene and the incidence of STH coinfection in TB patients in Tempurejo Sub-District, Jember District. This type of research is observational research with cross sectional analytic design. The population used was TB patients in Tempurejo Sub-District in the period September - October 2019. The data used in this study were primary data in the form of interviews and results of stool examination. Stool examination is carried out using the sedimentation and floatation methods. Data analysis was performed using Fisher's exact test. The results of this study indicate that the incidence of STH co-infection in TB patients in Tempurejo Subdistrict is 9.67% and is caused by two STH species, A. lumbricoides (66.7%) and Hookworm (33.3%). Respondents' personal hygiene consisted of good hygiene (64.5%) and bad hygiene (35.5%), where 66.7% of cases of STH coinfection occurred in respondents with poor personal hygiene. Fisher's test results showed that there was no significant relationship between personal hygiene with the incidence of STH coinfection in TB patients in Tempurejo Sub-District, Jember District (p-value of 0.281).